Mechanical properties of the liner for strengthening steel pipe under the action of normal fault - Kejie Zhai; Deqiang Hu; Kaidong Wang; Hongyuan Fang; Niannian Wang; Bin Li; Xueming Du; Yuquan Hu; Xiangqian Fan (Journal of Pipeline Science and Engineering)
Using liner pipe to rehabilitate pressure pipe can effectively improve the mechanical performance of the pipe. To explore the mechanical properties of the liner for repairing pressure pipes under the action of a normal fault, a refined three-dimensional (3D) finite element (FE) model is established and assessed by experiments and FE results. Then, the stress distribution of the liner is analyzed, and the effects of fault slip distance, slip angle, pipe diameter, host thickness, internal pressure, liner elastic modulus, and friction factor on the liner stress and vertical displacement are studied. Finally, the bearing capacity of the pipeline against normal faults is analyzed. The study shows that the distribution morphology of the crown and shoulder is similar and opposite to the distribution morphology of the invert and haunch. The crown and invert stress of the pipe is the highest, while the stress on the springline is the lowest. When the host pipe thicknesses are 3.0 mm, 3.5 mm, 4.0 mm, and 5.0 mm, the slip distance reaches 309 mm, 342 mm, 370 mm, and 449 mm, respectively, and the liner will damage at the crown.